Upaya Guru dalam Meningkatkan Kemampuan Literasi Numerasi Pada Siswa Kelas V di SDN Lebaksari Sukabumi - Fitriani Lestari Fitri; Agung Muttaqien; Fauziyatul Hamamy (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the efforts of teacher’s inimprove the ability of numeracy literacy in class V students at State Primary School (SDN) Lebaksari Sukabumi. This research is a type of qualitative research with a case study method. Data collection techniques using observation, interviews, documentation, and test. The data analysis procedure uses Miles and Huberman, through data reduction, data presentation, and drawing conclusions. Based on the results of the study 7% of students' numeracy skills were in the high category, 86% of students' numeracy skills were moderate and 7% of students' numeracy skills were low. So that the numeracy skills of class V students are in the moderate category. Teachers' efforts to improve numeracy literacy are by providing motivation and support to students, collaborating with parents of students, overcoming student anxiety, applying concepts in learning, implementing numeracy strengthening strategies, designing project-based learning, improving thinking skills students' critical thinking by discussing and linking numeracy elements to other subjects. Factors supporting teachers in improving student abilities are the support of the principal, parental support, reading corner, and information and communication technologi in the form of a computer. The inhibiting factors for teachers in improving students' numeracy skills are the unprepared tools to be used, the lack of non-learning reading books and the lack of training